Long-term health-related quality of life in persons diagnosed with an insulinoma in Finland 1980-2010 - Elina Peltola; Päivi Hannula; Heini Huhtala; Harri Sintonen; Saara Metso; Juhani Sand; Johanna Laukkarinen; Mirja Tiikkainen; Camilla Schalin‐Jäntti; Jukka Sirén; Minna Soinio; Pirjo Nuutila; et al. (Wiley, 2022)
Objective Insulinomas are rare pancreatic neoplasms, which can usually be cured by surgery. As the diagnostic delay is often long and the prolonged hyperinsulinemia may have long-term effects on health and the quality of life, we studied the long-term health-related quality of life (HRQoL) in insulinoma patients.Design, patients and measurements The HRQoL of adults diagnosed with an insulinoma in Finland in 1980-2010 was studied with the 15D instrument, and the results were compared to those of an age- and gender-matched sample of the general population. The minimum clinically important difference in the total 15D score has been defined as +/- 0.015. The clinical characteristics, details of insulinoma diagnosis and treatment, and the current health status of the subjects were examined to specify the possible determinants of long-term HRQoL.Results Thirty-eight insulinoma patients participated in the HRQoL survey (response rate 75%). All had undergone surgery with a curative aim, a median of 13 (min 7, max 34) years before the survey. The insulinoma patients had a clinically importantly and statistically significantly better mean 15D score compared with the controls (0.930 +/- 0.072 vs 0.903 +/- 0.039, P = .046) and were significantly better off regarding mobility, usual activities and eating. Among the insulinoma patients, younger age at the time of survey, higher level of education and smaller number of chronic diseases were associated with better overall HRQoL.Conclusions In the long term, the overall HRQoL of insulinoma patients is slightly better than that of the general population.